1985
DOI: 10.1063/1.448635
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical a bi n i t i o and low-temperature ESR study of the cyclohexane cation

Abstract: The cyclohexane cation has been studied theoretically using ab initio MO-LCAO-UHF calculations, as well as experimentally, by means of low-temperature ESR measurements in a CF3CCl3 matrix between 4 and 140 K. It is found that the most stable conformation of the free cation is a distorted chair conformation with Cs symmetry, with one carbon atom being separated from the others by bonds that are approximately 0.1 Å larger than the remaining C–C bonds. The symmetrical chair conformation of C2h symmetry is predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Focusing on the former picture, the non-degenerate A ′ and A ′′ states arise from a degenerate pair of eg molecular orbitals in cyclohexane by symmetry breaking due to the halogen substituent and the interaction of the ring with the halogen lone pair, which is reminiscent of Jahn-Teller coupling in the cyclohexane cation. 71 In C S symmetry, the p-type halogen lone pair electron hole in the cation may either be symmetric or antisymmetric, i.e., aligned perpendicular to or parallel with the C 6 ring. This is also clearly seen in the Dyson orbitals in Fig.…”
Section: Geometry Relaxation Upon Ionizationmentioning
confidence: 99%
“…Focusing on the former picture, the non-degenerate A ′ and A ′′ states arise from a degenerate pair of eg molecular orbitals in cyclohexane by symmetry breaking due to the halogen substituent and the interaction of the ring with the halogen lone pair, which is reminiscent of Jahn-Teller coupling in the cyclohexane cation. 71 In C S symmetry, the p-type halogen lone pair electron hole in the cation may either be symmetric or antisymmetric, i.e., aligned perpendicular to or parallel with the C 6 ring. This is also clearly seen in the Dyson orbitals in Fig.…”
Section: Geometry Relaxation Upon Ionizationmentioning
confidence: 99%
“…Since in Freon the cis and trans isomers give similar ESR spectra at nitrogen temperatures, the dramatic difference observed in their OD ESR spectra in alkane matrices deserves special consideration. It is well-known that in radical cations of many cyclic alkanes (e.g., cyclohexane) the intramolecular dynamic transitions between degenerate Jahn−Teller states can take place. ,, The latter leads to the modulation of hyperfine coupling constants, which should reveal itself in the OD ESR spectra. It is believed that a strong anisotropy and large shift of g -factor, typical of these Jahn−Teller active radical cations, result from the admixture of orbital state, which also shortens the spin−lattice relaxation times.…”
Section: Od Esr Studiesmentioning
confidence: 99%
“…It should be remarked that there is no reason for the three distorted structures to have an equal potential energy in the frozen matrix, thus an nonequivalent averaging naturally occurs, which yields three sets of hyperfine couplings instead of two sets expected for the cation with C2h symmetry. This interpretation is reasonably extended to the cation in Fil before annealing as well as to that in CF3CCI 3 [11], and gives confirmation that these cyclohexane cations have a C2h structure induced by JT distortion for the system without dynamics [9].…”
Section: Matrix Effect On the Dynamicsmentioning
confidence: 85%
“…It has been revealed that cyclohexane cation in frozen matrices has an elongated chair forra (C2h) with the unpaired electron in ag orbital ( Fig. la), which is derived from a regular chair form of D3d due to JT distortion [9][10][11]. The observed hyperfine structure was attributed to the three pairs of equatorial protons (hyperfine structure constants (hfc's) are 8.5, 3.4, and 1.4 mT in CFC13), which are derived from partial and non equivalent averaging between the three C2h conformers (see Fig.…”
Section: Introductionmentioning
confidence: 99%